(untitled) (Berlin, 2005)
This book constitutes the refereed proceedings of the Second International Conference on Cooperative Design, Visualization, and Engineering, CDVE 2005, held in Palma de Mallorca, Spain, in September 2005.
Keywords: Computer-aided design,Engineering design,Architectural design,CAD,Thiết kế Kỹ thuật,Thiết kế kiến trúc; Data processing,Data processing,Xử lý dữ liệu,Xử lý dữ liệu